Home Worker: Business Dynamics and Family Resilience (Case Study in Sanan Tempe Chips Village, Malang City) - Wahyuni, Sri; Sopingi, Sopingi; Apriani, Rizka (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
Urban life demands struggle and competition for each individual to survive. Job opportunities are sometimes not proportional to the population, so people are required to be able to create jobs independently. This condition has triggered the emergence of home workers (honme workers). Sanan Village is one of the central villages for the tempeh chips industry in Malang City which has succeeded in raising its community to become more empowered. The aim of this research is to explain the business dynamics and strategies used by home workers to maintain their business to build family resilience and explain the basic valuesthat serve as their working principles. This research is qualitative research with a case study design. Data collection was carried out through in-depth interviews, observations and document studies and analyzed using interactive analysis techniques. Research informants were selected purposively with certain criteria according to the research focus.The results of this research show that home workers are able to maintain their businesses. Business dynamics starting from starting a business, maintaining a business, and developing a business can be handled using various strategies. The results of the business can be used to support or fulfill the needs of the family and to send their children to college. The efforts made by home workers are socially capable of creating jobs. The valuesand principles held by home workers are to work honestly, work hard and always be grateful.Keywords: : home workers, family resilience, Sanan village.